Theatre Reviews - Georgopoulou, Xenia; Pilla, Eleni; Kizelbach, Urszula; Fabiszak, Jacek (Multicultural Shakespeare: Translation, Appropriation and Performance, 2015)
Romeo and Juliet for Two. Dir. Kostas Gakis, Athina Moustaka, Konstantinos Bibis. 104 Theatre, Athens, Greece.Lady Macbeth. Dir. Marios Mettis. Theatro Thentro, Nicosia, CyprusHamlet. Dir. Jan Klata. Gdańsk Shakespeare Theatre, Gdańsk, PolandThe Taming of the Shrew [Poskromienie złośnicy]. Dir. Katarzyna Deszcz. Stefan Żeromski Theatre, Kielce, Poland